Compounded Exclusion: Education for Disabled Refugees in Sub-Saharan Africa - Walton, Elizabeth; McIntyre, Joanna; Awidi, Salome Joy; De Wet-Billings, Nicole; Dixon, Kerryn; Madziva, Roda; Monk, David; Nyoni, Chamunogwa; Thondhlana, Juliet; Wedekind, Volker (Frontiers in Education, 2020)
International conventions acknowledge the right of refugees and of disabled people to access quality inclusive education. Both groups struggle to assert this right, particularly in the Global South, where educational access may be hindered by system constraints, resource limitations and negative attitudes. Our concern is the intersectional and compounding effect of being a disabled refugee in Sub-Saharan Africa. Disabled refugees have been invisible in policy and service provision, reliable data is very limited, and there has been little research into their experiences of educational inclusion and exclusion. This article makes the case for research to address this gap. Three country contexts (South Africa, Zimbabwe and Uganda) are presented to illustrate the multi-layered barriers and challenges to realizing the rights for disabled refugees in educational policy and practice. These three countries host refugees who have fled civil unrest and military conflict, economic collapse and natural disaster, and all have signed the United Nations Convention on the Rights of Persons with Disabilities. None has available and reliable data about the numbers of disabled refugees, and there is no published research about their access to education. Arguing for an inclusive and intersectional approach and for the importance of place and history, we illustrate the complexity of the challenge. This complexity demands conceptual resources that account for several iterative and mutually constituting factors that may enable or constrain access to education. These include legislation and policy, bureaucracy and resource capacity, schools and educational institutions, and community beliefs and attitudes. We conclude with a call for accurate data to inform policy and enable monitoring and evaluation. We advocate for the realization of the right to education for disabled refugee students and progress towards the realization of quality inclusive education for all.